Management of maxillary first molar with six canals using operating microscope - K V Kishan; Devika Das; Naveen Chhabra; Vishnu Pratap Singh Rathore; Vimal Remy (Wolters Kluwer Medknow Publications, 2018)
The purpose of this article was to highlight the importance of having a thorough knowledge about the root canal morphology. This case report highlights the unusual anatomy of a maxillary first molar with three mesiobuccal (MB) canals, two palatal canals, and one distobuccal canal which is extremely rare. The use of operating microscope was crucial, both for the detection and for the management of the additional canals. The use of surgical operating microscope and digital radiograph showed that MB root had Type 3-1 of Gulabivala classification and palatal canal showed Vertucci's Type II canal morphology This report describes and discusses the identification of variation in canal morphology of maxillary first molar and the use of latest adjuncts in successfully diagnosing and negotiating them.